The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/jemt.10289
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal regeneration after cavity preparation, with special reference to close spatio‐relationships between odontoblasts and immunocompetent cells

Abstract: The regeneration process of the odontoblast cell layer incident to tooth injury, especially its relationship with immunocompetent cells in pulp healing, has not been fully understood. The purpose of the present study was to clarify this relationship between odontoblasts and immunocompetent cells in the process of pulp regeneration following cavity preparation in rat molars by immunocytochemistry for heat shock protein (Hsp) 25 as well as class II major histocompatibility complex (MHC) molecules. In untreated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 42 publications
4
48
2
3
Order By: Relevance
“…This finding is different from that reported by Schmalz et al (2001) who have shown that SV40 large T-antigen-transfected bovine pulp-derived cells proliferate extensively on processed dentin and do not show odontoblast-like morphology after 14 days. Whereas recent reports suggest that newly differentiated odontoblasts extend their processes into existing dentinal tubules after pulp injury in rats in an in vivo setting (Nakakura- Ohshima et al 2003;Ohshima et al 2003), our finding is the first evidence for the phenomenon that human pulp cells of odontoblast-lineage differentiate into odontoblasts in vitro upon contact with dentin, even if it has been treated mechanically and chemically. The chemical treatment of dentin (e.g., by EDTA) may solubilize various noncollagenous dentin matrix components and growth factors, such as transforming growth factor-β1, which may have an inductive effect on the differentiation of odontoblast progenitor cells (Smith 2002).…”
Section: Discussioncontrasting
confidence: 74%
“…This finding is different from that reported by Schmalz et al (2001) who have shown that SV40 large T-antigen-transfected bovine pulp-derived cells proliferate extensively on processed dentin and do not show odontoblast-like morphology after 14 days. Whereas recent reports suggest that newly differentiated odontoblasts extend their processes into existing dentinal tubules after pulp injury in rats in an in vivo setting (Nakakura- Ohshima et al 2003;Ohshima et al 2003), our finding is the first evidence for the phenomenon that human pulp cells of odontoblast-lineage differentiate into odontoblasts in vitro upon contact with dentin, even if it has been treated mechanically and chemically. The chemical treatment of dentin (e.g., by EDTA) may solubilize various noncollagenous dentin matrix components and growth factors, such as transforming growth factor-β1, which may have an inductive effect on the differentiation of odontoblast progenitor cells (Smith 2002).…”
Section: Discussioncontrasting
confidence: 74%
“…Tooth replantation induces extensive degeneration of almost all odontoblasts 1 day after operation (Nakakura- Ohshima et al 2003), showing that this type is the heavy injury model. Control dental pulp (6 weeks after birth) was composed of three layers: a diVerentiated odontoblast layer, a subodontoblastic layer including a cell-rich zone and the center of the pulp tissue (Fig.…”
Section: Responses Of Lrcs Against Tooth Replantation (Heavy Injury Mmentioning
confidence: 98%
“…The procedures of cavity preparation and tooth replantation induce destructive changes in odontoblasts at the aVected site as well as an acute inXammatory reaction in rat molars (Nakakura- Ohshima et al 2003;Ohshima 1990;Ohshima et al 2003). In these experimental models, pulpal mesenchymal cells take the place of the degenerated odontoblasts to diVerentiate into odontoblastlike cells resulting in the formation of reparative dentin, although the extent of aVected odontoblasts diVers between these diVerent models.…”
Section: Introductionmentioning
confidence: 96%
“…Tooth replantation/transplantation induces at least two types of healing patterns in the replanted teeth: dentin and bone tissue formation in the repaired dental pulp (Byers et al 1992;Hasegawa et al 2007;Kvinnsland et al 1991;Ohshima et al 2001;Rungvechvuttivittaya et al 1998;Shimizu et al 2000;Tsukamoto-Tanaka et al 2006;Unno et al 2009). Our recent studies have demonstrated that the types of cells appearing along the pulp-dentin border play crucial roles in determining the healing patterns in the replanted teeth: once osteoclast lineage cells appear at the pulp-dentin border, bone matrix deposition can be induced (Hasegawa et al 2007;Tsukamoto-Tanaka et al 2006;Unno et al 2009), whereas the temporal appearance of dendritic cells there induces dentin formation (Nakakura- Ohshima et al 2003;Shimizu et al 2000). Thus, the temporal appearance of dendritic cells at the pulp-dentin border is suggestive of a decisive phenomenon to induce the odontoblast differentiation during the pulpal healing process following tooth injuries (Nakakura- Ohshima et al 2003).…”
mentioning
confidence: 99%